2002
DOI: 10.1108/14668203200200002
|View full text |Cite
|
Sign up to set email alerts
|

The response to No Secrets

Abstract: This article reports the results of a survey of local authorities, which asked about progress in responding to the Department of Health guidance, No Secrets. The findings of the survey suggest that the majority of local authorities are taking action in response to the guidance. However, there is variation in progress with the different components of the framework for the protection of vulnerable adults outlined in No Secrets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 1 publication
2
17
0
Order By: Relevance
“…A comparison, then, cannot be made about the levels of consultation of people with learning difficulties between the survey reported for this article (before No Secrets) and the Mathew et al (2002) survey (after No Secrets). The Mathew et al (2002) survey does, however, tell us that in terms of the membership of adult protection committees, 31% of local authorities included user or carer groups. Unfortunately for the purposes of this report, the survey does not separate out users and carers, let alone specifically identify people with learning difficulties.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A comparison, then, cannot be made about the levels of consultation of people with learning difficulties between the survey reported for this article (before No Secrets) and the Mathew et al (2002) survey (after No Secrets). The Mathew et al (2002) survey does, however, tell us that in terms of the membership of adult protection committees, 31% of local authorities included user or carer groups. Unfortunately for the purposes of this report, the survey does not separate out users and carers, let alone specifically identify people with learning difficulties.…”
Section: Discussionmentioning
confidence: 95%
“…Having conducted a survey of local authority progress in implementing No Secrets, Mathew et al (2002) asked SSDs in England to what extent they had consulted various agencies in the development of multi-agency adult protection policy (including user groups). Respondents to the survey had to indicate the level of consultation, on a scale of one to five, where one is no contact and five is full consultation and inclusion in decisionmaking groups.…”
Section: Discussionmentioning
confidence: 99%
“…This agency, the Criminal Records Bureau (CRB), offers organisations a 'one-stop-shop' for checking the suitability of potential employees to work with adults in health and social care settings. Matthew et al (2002) state that: 'It will be necessary to consider how the No Secrets framework will dovetail with the plethora of changes arriving in 2002, which include changes to professional regulation and inspection (National Care Standards Commission) and the Criminal Records Bureau. ' No Secrets assigns the task of co-ordinating multi-agency adult protection procedures to social services as lead agency, This document aims to establish a framework, which runs in parallel to that which exists for children, although noting important differences in law and in the balance to be struck between supporting autonomy and acting protectively.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that there have been very different responses and identified resources to match the requirement to establish formal mechanisms to deal with allegations of the abuse of vulnerable adults. Although most local authorities have set up an adult protection unit (APU) to lead and co-ordinate local adult protection strategies, there are wide variations in the approach adopted by different authorities in England (Mathew et al, 2002;Sumner, 2004).…”
Section: Contextmentioning
confidence: 99%